Proceedings of the Ocean Drilling Program 1993
DOI: 10.2973/odp.proc.sr.130.051.1993
|View full text |Cite
|
Sign up to set email alerts
|

Neogene Carbonate Sedimentation on Ontong Java Plateau: Highlights and Open Questions

Abstract: Neogene ocean history is dominated by the theme of stepwise global cooling (with occasional reversals); the main trends of carbonate sedimentation on the Ontong Java Plateau show the regional response of productivity, dissolution, winnowing, and redeposition to this overall climatic change. The relative importance of these processes in controlling accumulation rates and carbonate content is difficult to assess for any given place and time. Thus, the outstanding feature of the carbonate record, the Tortonian-Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
67
0

Year Published

1995
1995
2016
2016

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(68 citation statements)
references
References 67 publications
1
67
0
Order By: Relevance
“…Similar observations have been made at other sites beneath upwelling regions of the Indian and Paci¢c oceans (e.g. Van Andel et al, 1975;Peterson et al, 1992;Berger et al, 1993;Farrell et al, 1995;Dickens and Owen, 1999). Records of CaCO 3 , Ba, opal, and organic carbon accumulation at ODP site 850 in the eastern Equatorial Paci¢c (Schroeder et al, 1997) are especially pertinent for comparison.…”
Section: The Timing Of Enhanced Productivitymentioning
confidence: 52%
“…Similar observations have been made at other sites beneath upwelling regions of the Indian and Paci¢c oceans (e.g. Van Andel et al, 1975;Peterson et al, 1992;Berger et al, 1993;Farrell et al, 1995;Dickens and Owen, 1999). Records of CaCO 3 , Ba, opal, and organic carbon accumulation at ODP site 850 in the eastern Equatorial Paci¢c (Schroeder et al, 1997) are especially pertinent for comparison.…”
Section: The Timing Of Enhanced Productivitymentioning
confidence: 52%
“…We suggest (1) that it is hardly likely that such dramatic changes in the eastern Pacific Ocean could occur without repercussion in other parts of the global climate system and (2) that efforts should be made to identify related changes in other regions with a view to identifying the cause. Certainly, analogous changes have been reported in the equatorial Indian Ocean (Peterson and Backman, 1990) as well as in the western equatorial Pacific (Berger et al, 1993).…”
Section: Sedimentation Ratesmentioning
confidence: 69%
“…Although this may indeed be the ramification of the onset of NADW, Berger (1970) and suggested that the initiation and increase of NADW flow would tend to suppress the upwelling of AABW in the south Atlantic and increase the flow of more corrosive AABW into the Pacific (basin-basin fractionation). Berger et al (1993) elaborated on these arguments but tried to explain the chemical history of the western equatorial Pacific, calling NADW "the master modulator." Farrell et al (this volume), however, take a detailed look at the history of NADW (converted to the Leg 138 time scale) and fail to find synchroneity between NADW behavior (as outlined by Bohrmann et al, 1990, and Wright et al, 1991, 1992 and the history of sedimentation in the eastern equatorial Pacific, though the ability to make such detailed temporal comparisons must be questioned.…”
Section: Middle/late Miocene Carbonate Transitionmentioning
confidence: 99%